2010
DOI: 10.1017/s1935789300002391
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Disasters on Populations With Health and Health Care Disparities

Abstract: Context A disaster is indiscriminate in whom it affects. Limited research has shown that the poor and medically underserved, especially in rural areas, bear an inequitable amount of the burden. Objective To review the literature on the combined effects of a disaster and living in an area with existing health or health care disparities on a community’s health, access to health resources, and quality of life. Methods We performed a systematic literature review using the following search terms: disaster, heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
89
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 98 publications
(93 citation statements)
references
References 120 publications
3
89
0
1
Order By: Relevance
“…4-7 While surge capacity refers to the provision of medical care to a large volume of persons during the acute response 8 ; we define secondary surge capacity as the sustained ability of a health care system to expand operational resources to meet the increased and/or fluctuating demand for medical care services throughout long-term recovery. The current disaster literature has examined surge capacity constraints during the initial response 9,10 , but has largely overlooked the surging demand in health services to address the ballooning of incident or existing chronic disease in the aftermath of a disaster.…”
Section: Introductionmentioning
confidence: 99%
“…4-7 While surge capacity refers to the provision of medical care to a large volume of persons during the acute response 8 ; we define secondary surge capacity as the sustained ability of a health care system to expand operational resources to meet the increased and/or fluctuating demand for medical care services throughout long-term recovery. The current disaster literature has examined surge capacity constraints during the initial response 9,10 , but has largely overlooked the surging demand in health services to address the ballooning of incident or existing chronic disease in the aftermath of a disaster.…”
Section: Introductionmentioning
confidence: 99%
“…11 Davis et al found that few studies focused on the specific impact of disasters on preexisting health disparities. 12 …”
mentioning
confidence: 99%
“…As the other disasters have previously illustrated, there is a constant struggle to mitigate selection bias in epidemiologic studies of disaster populations. This is even more of a concern when there is the likelihood of health disparities across race [47] and lack of trust in public officials who some may think should have prevented the EPHD. Distrust is a very normal response because trust has been broken in EPHDs, and such affected communities are often already socio-economically disadvantaged [48].…”
Section: Resultsmentioning
confidence: 99%